COVID-19 and haemodynamic failure: a point of view on mechanisms and treatment - Jasiński, Tomasz; Stefaniak, Jan (Anestezjologia Intensywna Terapia, 2020)
The SARS-CoV-2-related disease has an undoubted impact on the healthcare system. In the treatment of severe COVID-19 cases, the main focus is on respiratory failure. However, available data suggest an important contribution of haemodynamic impairment in the course of this disease. SARS-CoV-2 may affect the circulatory system in various ways that are universal for septic conditions. Nonetheless, unique features of this pathogen, e.g. direct insult leading to myocarditis and renin-angiotensin-aldosterone axis dysregulation, must be taken into account. Although current recommendations on COVID-19 resemble previous septic shock guidelines, special attention to haemodynamic monitoring and treatment is necessary. Regarding treatment, one must take into account the potential profound hypovolaemia of severe COVID-19 patients. Pharmacological cardiovascular support should follow existing guidelines and practice. Interesting concepts of decatecholaminisation and the effect of vasopressors on pulmonary circulation are also presented in this review on COVID-19-related haemodynamic failure.